A Sustainable Training Strategy for Improving Health Care Following a Catastrophic Radiological or Nuclear Incident. Issue 1 (12th February 2014) - Blumenthal, Daniel J.; Bader, Judith L.; Christensen, Doran; Koerner, John; Cuellar, John; Hinds, Sidney; Crapo, John; Glassman, Erik; Potter, A. Bradley; Singletary, Lynda
Abstract: The detonation of a nuclear device in a US city would be catastrophic. Enormous loss of life and injuries would characterize an incident with profound human, political, social, and economic implications. Nevertheless, most responders have not received sufficient training about ionizing radiation, principles of radiation safety, or managing, diagnosing, and treating radiation-related injuries and illnesses. Members throughout the health care delivery system, including medical first responders, hospital first receivers, and health care institution support personnel such as janitors, hospital administrators, and security personnel, lack radiation-related training. This lack of knowledge can lead to failure of these groups to respond appropriately after a nuclear detonation or other major radiation incident and limit the effectiveness of the medical response and recovery effort. Efficacy of the response can be improved by getting each group the information it needs to do its job. This paper proposes a sustainable training strategy for spreading curricula throughout the necessary communities. It classifies the members of the health care delivery system into four tiers and identifies tasks for each tier and the radiation-relevant knowledge needed to perform these tasks. By providing education through additional modules to existing training structures, connecting radioactive contamination control to daily professional practices, and augmenting these systems with just-in-time training, the strategy creates a sustainable mechanism for giving members of the health care community improved ability to respond during a radiological or nuclear crisis, reducing fatalities, mitigating injuries, and improving the resiliency of the community. D Blumethal, J Bader, D Christensen, J Koerner, J Cuellar, S Hinds, J Crapo, ES Glassman, AB Potter, L Singletary .A sustainable training strategy for improving health care following a catastrophic radiological or nuclear incident .Prehosp Disaster Med .2014 ;29 (1 ):80 -86 .